1996
DOI: 10.1093/jn/126.suppl_4.1187s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin K on Bone Mass and Bone Metabolism

Abstract: Vitamin K is involved in blood coagulation and in bone metabolism via the carboxylation of glutamate residues in (hepatic) blood coagulation factors and (osteoblastic) bone proteins. The bioavailability of nutritional vitamin K depends on the type of food, the dietary fat content, the length of the aliphatic side chain in the K-vitamer and probably also the genetically determined polymorphism of apolipoprotein E. Although undercarboxylation of blood coagulation factors is very rare, undercarboxylated osteocalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 33 publications
0
39
0
2
Order By: Relevance
“…Vitamin K interferes with bone quality through its action on the osteocalcin carboxylation, improving the protein-hydroxyapatite bound capacity (Vermeer et al, 1996) Some studies (Binkey et al, 1995;Vermeer et al, 1996;Booth, 1997) have also reported a modulating effect of carboxylated osteocalcin on bone matrix mineralization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin K interferes with bone quality through its action on the osteocalcin carboxylation, improving the protein-hydroxyapatite bound capacity (Vermeer et al, 1996) Some studies (Binkey et al, 1995;Vermeer et al, 1996;Booth, 1997) have also reported a modulating effect of carboxylated osteocalcin on bone matrix mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…Vermeer et al (1996) reported that vitamin K is involved in blood coagulation and bone metabolism via carboxylation reaction in which glutamic acid residues (GLA) transform the g-carboxyglutamic glutamatic acid into blood coagulation factors and bone proteins (osteocalcin, matrix GLA protein, and S protein). Osteocalcin is a low-weight molecular protein with three GLA residues produced by osteoblasts during bone matrix formation (Mijares et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, an increase in serum Glu-OC was demonstrated to increase the risk of bone fracture (9,10). Some investigators have reported that adult patients with hip fractures or spinal crush fractures had very low concentrations of circulating PK and MK (11,12).…”
mentioning
confidence: 99%
“…The dietary necessity and physiological roles of vita min K are fairly well established for mammals (1) and its importance in bone health has recently been a focus for research (2). However, it is still not clear whether di etary supplementation of this vitamin is indispensable for the growth of fish because contradictory results have been reported between fish species (3)(4)(5)(6).…”
mentioning
confidence: 99%